No change in developmental outcome with incubator covers and nesting for very preterm infants in a randomised controlled trial. Issue 2 (14th August 2008) - Maguire, C M; Walther, F J; van Zwieten, P H T; Le Cessie, S; Wit, J M; Veen, S
Abstract : Objective: To investigate in a randomised controlled trial the effect of basic elements of developmental care (incubator covers and positioning aids) on growth and neurodevelopment in infants born at < 32 weeks. Method: Infants were randomised within 48 h of birth to a developmental care (DC) or standard care (C) group. Outcome measures at 1 and 2 years corrected age were growth, standardised neurological examinations, and mental (MDI) and psychomotor (PDI) development (Dutch version of the Bayley Scales of Infant Development II). Results: 192 infants were recruited (DC = 98; C = 94). Thirteen infants (DC = 7, C = 6) were excluded because they were admitted for <5 days or died within the first 5 days. In total, 179 infants met the inclusion criteria. In-hospital mortality was 12/91 (13.2%) in the DC group and 8/88 (9.1%) in the C group. Assessments were carried out on 147 children (DC = 74, C = 73) at 1 year and 142 children (DC = 72, C = 70) at 2 years. No significant difference in growth, neurological outcomes or MDI was found. A positive trend in PDI at 1 year (p = 0.05) did not continue once the children reached 2 years. There was no difference found when neurological and developmental scores were combined. Conclusions: Basic developmental care has no positive effect on neurological and mental development or growth at 1 and 2 years of age in infants born at <32 weeks. A positive effect on psychomotor development at 1 year did not continue at 2 years of age. Trial registration number: ISRCTN84995192.